PENGARUH SIKAP DAN FASHION LEADERSHIP TERHADAP NIAT BELI ONLINE REMAJA di KOTA DENPASAR - Dwipayani, Ni Made; Rahyuda, I Ketut (E-Jurnal Manajemen; Vol 5 No 6 (2016), 2016)
The main purpose study describes the effect of attitudes towards the online purchase intention teenagers in Denpasar, describes the influence of fashion leadership on online purchase intention teenagers in Denpasar and prove the influence of attitude and fashion leadership of the online purchase intention teenagers in Denpasar.The location research is in Denpasar and used multiple linear regression analysis techique.The amount of sample as 100 respondents which were determined used is purposive sampling method. Results of regression models provide answers attitude and fashion leadership simultaneous effect on online purchase intention teenagers in Denpasar. Attitude and fashion leadership partial significant positive effect on online purchase intention teenagers in Denpasar.Recommended for fashion online providers to give clear, complete and accurate information on the procedures for product ordering and payment, delivery procedure and the return or exchange products, so as to encourage an attitude of consumers to make purchases online.
Keywords: attitude; fashion leadership; purchase intention